The effect of human capital on income inequality across provinces in Vietnam - Ho, Chi Minh (Edelweiss Applied Science and Technology, 2025)
Human capital is a nation’s primary resource and an internal strength for achieving sustainable economic growth and development. Conversely, income inequality is a critical factor influencing sustainable growth and social transformation, especially in developing countries. This paper investigates the impact of human capital on income inequality at the provincial level within the Vietnamese context. Based on learning theory and the Kuznets hypothesis, we employ spatial regression, threshold regression, and instrumental variable regression to examine the effect of human capital on income inequality in Vietnam from 2016 to 2020. The findings indicate that human capital reduces income inequality across provinces in Vietnam. However, economic growth exhibits a U-shaped relationship with income inequality. Urbanization tends to decrease income inequality in disadvantaged provinces, whereas the services sector increases inequality. Foreign direct investment (FDI) tends to widen the income gap in Vietnam due to uneven benefits across provinces. These findings suggest that social policies aimed at reducing income inequality should focus on enhancing human capital and promoting urbanization. Additionally, the structure of the national economy should be balanced across sectors to attract FDI into various provinces, thereby fostering economic growth and reducing income inequality. Based on these insights, Vietnam can achieve sustainable economic growth, development, and social transformation in the future.